The use of continuous vs. intermittent cold water immersion as a recovery method in basketball players after training: a randomized controlled trial. Issue 2 (3rd April 2017) - Sánchez–Ureña, Braulio; Martínez–Guardado, Ismael; Crespo, Carmen; Timón, Rafael; Calleja-González, Julio; Ibañez, Sergio J.; Olcina, Guillermo
ABSTRACT: Objectives : The main objective of this study was to compare two cold water immersion protocols, continuous or intermittent, on recovery in basketball players. Methods : Ten male basketball players (age: 14 ± 0.4 years, body mass: 65.4 ± 9.1 kg, height: 175 ± 7.3 cm, body fat %: 10.3 ± 4) were included in the study. After three 90-minute training sessions (avg. heart rate 158 ± 11.92, 156 ± 7.06 and 151 ± 10.44 bpm), participants were grouped into a continuous immersion (12 min at 12 ± 0.4°C) group, intermittent immersion (4 x 2 min immersion at 12 ± 0.4 °C + 1 min out of water) group and a control group (CG). Countermovement jump (CMJ), muscle pain and thigh volume were measured. Results : Both cold water immersion protocols were effective in reducing the pain 24 and 48 hours after training compared with the CG ( F (3.54) = 2.91, p  = 0.016, ηp 2   = .24). Concerning CMJ change, % differences occurred at 24 ( Z  = 11.04, p  = 0.004) and 48 hours ( Z  = 14.01, p  < 0.001) in comparison with the CG. Regarding the muscle volume, the statistical analysis did not report a significant interaction ( F (3.54) = 2.42, p  = 0.058). Conclusion : Both cold water immersion CWI protocols are effective in improving recovery in basketball players.